Effect of dynamic oscillation shear flow intensity on the mechanical and morphological properties of high-density polyethylene: An integrated experimental and molecular dynamics simulation study. (December 2019) - Liu, Tong; Li, Wei; Li, Lengwan; Peng, Xiangfang; Kuang, Tairong
Abstract: Dynamic oscillation shear flow-induced crystallization has been proved to be an effective approach to achieving high-performance semi-crystalline polymer (SCP) in recent years. In this study, a loop push-pull oscillatory molding (LOPPM) technology with controlled shear intensity was employed to investigate the processing-structure-property relationship in semi-crystalline high-density polyethylene (HDPE). The results of SEM, SAXS, and WAXD showed that the crystal structure of the samples changed significantly from skin to core layer such as refined spherulites and oriented shish-kebabs. The tensile strength, Young's modulus, and impact toughness firstly increased and then decreased with the enhanced shear flow field, exhibiting optimal shear intensity for mechanical properties. In particular, the tensile strength, Young's modulus, bending strength, bending modulus, and impact strength of HDPE sample under the optimal external shear intensity (LOPPM-M) were 176.2%, 124.5%, 129.2%, 243.6%, and 207.8% higher than those values of the conventional injection molding sample (CIM) respectively. Additionally, molecular dynamics simulations were adopted to explore the processing-structure relationship and the results showed good correspondence with the experimental findings. The strengthening-toughening mechanism and crystal evolution process were further discussed. Overall, this study provides valuable guidance for designing and fabricating SCP with tunable properties. Highlights: The optimal intensity of dynamic oscillation shear flow can dramatically improved the mechanical properties of HDPE. 2D-WAXD and 2D-SAXS are used to analysis the evolution of the crystals under different shear intensity. MD simulations results have proven the existence of the optimal shear intensity. Strengthening-toughening mechanism is discussed.